2015
DOI: 10.5152/dir.2014.14279
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging in the head and neck region: usefulness of apparent diffusion coefficient values for characterization of lesions

Abstract: ORIGINAL ARTICLE PURPOSEWe aimed to evaluate the role of apparent diffusion coefficient (ADC) values calculated from diffusion-weighted imaging for head and neck lesion characterization in daily routine, in comparison with histopathological results. METHODSNinety consecutive patients who underwent magnetic resonance imaging (MRI) at a university hospital for diagnosis of neck lesions were included in this prospective study. Diffusion-weighted echo-planar MRI was performed on a 1.5 T unit with b factor of 0 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 16 publications
(27 reference statements)
3
27
0
Order By: Relevance
“…In another study Zhang et al[ 32 ] reported additional value of ADC measurements in necrotic and solid portions. ADC calculations are also useful in monitoring the patient after chemo-radiotherapy and differentiation of recurrent tumors from post-treatment changes[ 28 , 29 , 33 , 34 ].…”
Section: Clinical Applications Of Dwimentioning
confidence: 99%
“…In another study Zhang et al[ 32 ] reported additional value of ADC measurements in necrotic and solid portions. ADC calculations are also useful in monitoring the patient after chemo-radiotherapy and differentiation of recurrent tumors from post-treatment changes[ 28 , 29 , 33 , 34 ].…”
Section: Clinical Applications Of Dwimentioning
confidence: 99%
“…Diagnosis of head and neck lesions is difficult due to the complicated anatomic structure and different histological components of the many tissues of the neck [ 1 ]. Imaging of oral and maxillofacial lesions is not only important for diagnosis of lesions, but also for differentiation of benign lesions from malignant lesions and staging of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years dynamic contrast-enhancement and diffusionweighted MRI sequences use entered in standart protocol of evaluating of parodid gland. Previous studies has claimed that these protocols did not help in the diagnosis of a parotid mass, but recent studies claim the contrary [9,10]. Dynamic contrast-enhancement sequence contributes to diagnosis of venous ectasia.…”
Section: Discussionmentioning
confidence: 99%